The Impact of Global Dynamic Capabilities on Governance Structure Choice of Partnership: The Moderating Effect of Ambidexterity - Ren, Guoying; Peng, Michael Yao-Ping (Frontiers in Psychology, 2021)
While research on multinational inter-organizational relationships has demonstrated that SMEs’ capabilities can be developed via partnerships, we lack studies that relate the development of such capabilities to the management of business governance structure. The study provides a new perspective on internationalized SMEs marketing strategies in the global context. Using a dynamic capability view of the firm, the study develops hierarchical regression models linking global dynamic capabilities and governance structure. A study of 274 internationalized SME Taiwanese firms reveals that two key global dynamic capabilities, namely marketing and design. Our study suggests that internationalized SMSs strategically manage their autonomy and strategic options in choosing the appropriate combinations of different relationship types while they decide to develop global marketing capability, global design capability or both. The study also finds market orientation and learning orientation act as enabling mechanisms for building global dynamic capabilities.